2007
DOI: 10.1080/00288230709510280
|View full text |Cite
|
Sign up to set email alerts
|

Variation of lactoferrin and lactoperoxidase in bovine milk and the impact of level of pasture intake

Abstract: Lactoferrin (Lf) and lactoperoxidase (LP) are milk proteins with antimicrobial and immunomodulatory activities. This study examined the effect of pasture allowance on the production of Lf and activity of LP, as well as the variation in the concentration of Lf and activity of LP in the milk of lactating dairy cows during late lactation. Following a 2-week period where a herd of 20 cows was grazed solely on pasture, two different nutritional regimes were imposed upon the cows. For 4 weeks, 10 cows grazed ad libi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…On the other hand, Turner et al . () found that ad libitum access to pasture did not increase the lactoferrin concentration in milk. This was confirmed by Kuczyńska et al .…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, Turner et al . () found that ad libitum access to pasture did not increase the lactoferrin concentration in milk. This was confirmed by Kuczyńska et al .…”
Section: Resultsmentioning
confidence: 96%
“…Turner et al . (), analysing the lactoferrin content of the milk of cows using a pasture to various degrees, found a significantly ( P < 0.05) higher yield of this protein (in g per day) in the milk of cows having unrestricted access to pasture ( ad libitum ). It can be assumed that the bioactive compounds contained in green forages, which have immunomodulatory properties, have an indirect effect on lactoferrin levels.…”
Section: Resultsmentioning
confidence: 96%
“…The lactoferrin content of bovine colostrum is higher than in mature milk and constitutes an important element of innate immunity (Indyk & Filonzi, 2005). Its content in milk is determined largely genetically (Gajda-Morszewski & Śpiewak, 2015; Król et al, 2012;Turner, Thomson, & Auldist, 2007). Research also shows the effect of dietary factors on milk lactoferrin content (Król et al, 2012;Turner et al, 2003;Wielgosz, Sobczuk-Szul, Wroński, & Rzemieniewski, 2009).…”
Section: Discussionmentioning
confidence: 99%